PENDIDIKAN BERBASIS PENDIDIKAN BERBASIS KEUNGGULAN LOKAL PADA MADRASAH TSANAWIYAH DI KOTA MATARAM - Muhammad Zaki Athhar (Universitas Islam Negeri Mataram, Indonesia, 2019)
This study aims to describe in detail and analyze in depth the process of determination, forms of community participation, and implementation of local excellence education in tsanawiyah madrasas in the city of Mataram. The research method used is qualitative descriptive type. Data collection uses participatory observation techniques, in-depth interviews and documentation. Data analysis procedures rely on the narrative descriptive model ala Miles and Huberman in the form of data reduction, data presentation and verification. Based on data analysis, the results of the research can be described in the form of: (1) The process of determining local excellence into local excellence education is carried out through meetings, socialization, questionnaire distribution, and determination; (2) The form of limited community participation as teaching staff and trainers, does not involve relevant agencies, and traditional institutions in the community; and (3) Local excellence education is implemented through extracurricular activities in the form of rudat dance, and grouped into Art and Culture subjects in the form of music, especially sound art (Sasak regional songs). In addition to the results, this study also found that local excellence of rudat art does not have curriculum guidance, the process is direct to practice, and does not have assessment instruments. While local excellence through the subject of Arts and Culture uses the RPP tool downloaded from the internet, and does not make adjustments to the local excellence needs of the local area.